The Influence of Emotional Intelligence on Academic Achievement among University Students: The Mediating Role of Psychological Well-Being and the Moderating Role of Behavioral Academic Engagement (The International Journal of Educational Sciences and Arts, 2026)
This study aimed to examine the relationship between emotional intelligence and academic achievement among university students, investigate the mediating role of psychological well-being, and explore the moderating role of behavioral academic engagement in the relationship between psychological well-being and academic achievement.The study employed a quantitative, descriptive, correlational research design to analyze the relationships proposed in the research model. Data were collected using a questionnaire developed from previous studies and administered to a sample of 673 students from Palestinian universities. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM).The findings revealed a direct positive effect of emotional intelligence on both academic achievement and psychological well-being. In addition, psychological well-being was found to mediate the relationship between emotional intelligence and academic achievement, while behavioral academic engagement exerted a significant positive moderating effect on the relationship between psychological well-being and academic achievement.The study concluded that improving university students’ academic achievement can be more effectively achieved through the development of emotional and psychological resources, alongside the enhancement of behavioral academic engagement. Accordingly, the study recommended strengthening emotional intelligence and psychological well-being, integrating them into university curricula and educational practices, and adopting integrative educational models that combine psychological and behavioral dimensions, thereby substantially enhancing students’ academic achievement.
Keywords: Academic Achievement; Behavioral Academic Engagement; Psychological Well-being; Emotional Intelligence